Aplicación de Estrategias Didácticas de Solé para mejorar la Comprensión Lectora en los estudiantes de cuarto grado de Primaria Institución Educativa Experimental “Rafael Narváez Cadenillas” – Trujillo, 2016 - Mendoza Ortiz, Tamara Eliana (2017)
The present work of investigation had for principal aim determine in what measure the application of didactic strategies of Sole improves satisfactorily in the reading comprehension in the students of fourth degree of primary of the educational experimental Institution "Rafael Narváez Cadenillas", Trujillo - 2016._x000D_ The study realized with a sample population of 56 students of 4 ° degree, being the section "A" the group control and "B" the experimental group shaped by 28 students each of them. There was in use the type of applied investigation, using the quasiexperimental design; since instrument of compilation of information used a test of reading comprehension: Demonstrating what we know. The results of the investigation determined that the application of the didactic strategies of I Occurred it improved significantly in the reading comprehension in the students of group experimental